Islamic Educational Thought on STEM (Science, Technology, Engineering, Mathematics): Perspectives and Implementation - Aksan, Sahjad M; Zein, Muhammad; Saumur, Amanan S. (SAINTIS Publishing, 2023)
This research explores a new paradigm in Islamic educational thought regarding the integration of STEM (Science, Technology, Engineering, and Mathematics). The primary focus is on bridging the dichotomy between religious and secular sciences through an integrative approach grounded in the concept of tauhid (the oneness of God). Through this integration, STEM is seen as a means to comprehend the Ayat Kauniyah (signs of God in the universe), thereby positioning STEM learning as both an act of worship and a means of exploring God’s creation. The study also examines the implementation of the I-STEM model developed in Malaysia, which incorporates Islamic principles into STEM education. Although this paradigm shows great potential, significant challenges exist in its implementation, including gaps between philosophical conceptualization and practical application, as well as cultural resistance within certain communities. To address these challenges, initiatives such as the development of contextual teaching materials and teacher training programs have been introduced. The research underscores the importance of developing a STEM curriculum aligned with Islamic ethical values and highlights the contribution of STEM-Islam in character building and social ethics. Thus, integrating STEM into Islamic education can serve as a catalyst for scientific revival in the Muslim world without compromising its religious identity.